Analysis of relationship between interpersonal trust and social and economic indicators - Меркулова, Тамара Викторовна; Дзюба, Д. А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
The paper deals with the analysis of the type and the degree of relationship between the interpersonal trust index and social and economic indicators: Income (GDP per capita), Inequality (Gini coefficient), Human development index (HDI), Corruption (Corruption perception index). The methods of correlation analysis and neural network modeling are applied. The World Bank, World Values Survey (WVS) and European Social Survey (ESS) database is used. The analysis was carried out on the sample of 105 countries, where WVS and ESS interviews were conducted. The closest correlation dependence was found out between the trust index and HDI in a group of high human development countries, as well as among high income countries. The correlation is positive in these cases. In medium and low income level countries this relationship is weak and contradictory. The correlation between trust and corruption perception has similar nature: high income countries are characterized by close positive relationship between trust and corruption intolerance, in the low-income group this relationship is weaker, and in the group of middle income countries the correlation is negative. The weakest relationship is observed between the trust and GDP per capita (in the high income group it is positive, in the low income countries it is negative). There is negative weak correlation with Gini index in all the groups, except for the countries, where trust level is high: correlation dependence is strong there). Using a neural network model based on GDP per capita, the human development index and the corruption perception index, it was shown the possibility to predict the trust index for a group of high income countries.